STUDY OF SOLVATION EFFECT OF AMMONIUM SULPHATE AND AMMONIUM CHLORIDE FERTILIZER SOLUTIONS - K.RENUKA DEVI; S.RATHIKA (International Journal of Pharma and Bio Sciences, 2016)
The study of the properties of aqueous solutions is very important in many areas of science and researchers are progressing in this direction with a view to know more about the water structure. The ultrasonic velocity measurements are helpful to study the ion-solvent interaction in aqueous and non-aqueous solutions. The ammonical fertilizers of ammonium sulphate and ammonium chloride contain the nutrient nitrogen in the form of ammonium or ammonia. In this present investigation, ultrasonic velocity, density and viscosity of aqueous fertilizer solutions of ammonium sulphate and ammonium chloride were measured at various temperatures from 303ËšK to 323ËšK. The molal hydration number (nh), molar hydration number (nh1), apparent molal volume (φv), apparent molal compressibility (φk), limiting apparent molal volume (φvo), limiting apparent molal compressibility (φko), the constants (Sv & Sk) and molar solvated volume (φs) were determined using the measured values. The study of molar hydration number and molal hydration number reveals that there is a significant interaction between solute and solvent molecules due to which the structural arrangement in the neighbourhood of constituent solutes is considerably affected.